2017
DOI: 10.1111/jop.12561
|View full text |Cite
|
Sign up to set email alerts
|

Is chronic ulcerative stomatitis a variant of lichen planus, or a distinct disease?

Abstract: Chronic ulcerative stomatitis is an immune-mediated mucocutaneous disorder characterized clinically by erosions or ulcers. Most cases are limited to the mouth. The histopathological features are non-specific or mimic those of oral lichen planus, and studies by immunofluorescent microscopy are essential for definitive diagnosis. The defining immunopathogenic mechanism is the binding of IgG to the nuclear protein deltaNp63alpha of keratinocytes in the basal and parabasal cell layers of the oral stratified epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
1
15
1
Order By: Relevance
“…The oral manifestations of our 2 cases resembled OLP‐like lesion and DIF showed IgG and IgA staining at the nuclei of the basal and suprabasal area keratinocytes. Therefore, our findings from these cases are similar to those of a previous study that suggested that a CUS‐like lesion could be regarded as a variant of OLP, rather than as a distinct entity …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The oral manifestations of our 2 cases resembled OLP‐like lesion and DIF showed IgG and IgA staining at the nuclei of the basal and suprabasal area keratinocytes. Therefore, our findings from these cases are similar to those of a previous study that suggested that a CUS‐like lesion could be regarded as a variant of OLP, rather than as a distinct entity …”
Section: Discussionsupporting
confidence: 91%
“…In fact, there are many similarities between OLP and CUS, both clinically and histopathologically. DIF assays that show a granular or speckled pattern of IgG deposits within or surrounding the nuclei of keratinocytes of basal and parabasal layers of the affected stratified squamous cell epithelium are essential for the diagnosis . In our study, ENS was found in one case each in the OLL and OLDR groups.…”
Section: Discussionmentioning
confidence: 54%
“…Parodi et al tested the sera of 138 patients with skin or mucosal LP using monkey esophagus and HEp2‐2000 cells as substrates, and found SES‐ANAs directed against a 70 kDa antigen in 9 (7%) patients. These findings have led some to regard CUS as a variant of LP . However, the identity of this 70 kDa antigen is not entirely clear as it was not sequenced or detected with a control monoclonal antibody to ΔNp63α in the aforementioned study .…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, two of our patients carried a past diagnosis of oral LP. While epithelial nuclear IgG binding in CUS serves as a defining discriminator, autoantibodies directed to a 70 kDa antigen (presumably SES‐ANAs) have also been detected in the sera of some patients with LP . Parodi et al tested the sera of 138 patients with skin or mucosal LP using monkey esophagus and HEp2‐2000 cells as substrates, and found SES‐ANAs directed against a 70 kDa antigen in 9 (7%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…The immune-mediated diseases which persist after withdrawal of the suspected causative drug should be treated as being spontaneous idiopathic immune-mediated diseases. The objectives are to relieve symptoms, to promote healing, and to prolong periods of remission [ 14 ]. In general, highly potent topical or systemic glucocorticosteroids are the main pharmacological agents of choice, but severe cases of immune-mediated oral diseases may necessitate the use of other agents with immunosuppressive and/or anti-inflammatory properties [ 15 ].…”
Section: Introductionmentioning
confidence: 99%